Mechatronic systems : fundamentals - Isermann, Rolf (New York : Springer, 2005)
Annotation Many processes and systems manifest an increasing integration of mechanical and electronic components with information processing capacity. The development of such mechatronic systems opens the way to many innovative solutions not possible with mechanics or electronics alone.Mechatronic Systems introduces these developments by considering the dynamic modelling of components together with their interactions. The whole range of elements is presented from actuators, through different kinds of processes, to sensors.Structured tutorial style takes learning from the basics of unified theoretical modelling, through information processing to examples of system development. End-of-chapter exercises provide ready-made homework or self-tests. Offers practical advice for engineering derived from experience with real systems and application-oriented research. Written by one of the World's leading experts in this progressive field, Mechatronic Systems will be of great value to advanced students working in control, electrical and mechanical engineering and in areas where such definitions are being superseded. It will also prove useful to practising engineers wanting an in-depth understanding of how these disciplines and that of information processing are becoming interlinked.